Ketamine use for rapid sequence intubation in Australian and New Zealand emergency departments from 2010 to 2015: A registry study. (11th June 2018) - Ferguson, Ian; Alkhouri, Hatem; Fogg, Toby; Aneman, Anders
Abstract: Objective: This study aimed to quantify the proportion of patients undergoing rapid sequence intubation using ketamine in Australian and New Zealand EDs between 2010 and 2015. Methods: The Australian and New Zealand Emergency Department Airway Registry is a multicentre airway registry prospectively capturing data from 43 sites. Data on demographics and physiology, the attending staff and indication for intubation were recorded. The primary outcome was the annual percentage of patients intubated with ketamine. A logistic regression analysis was conducted to evaluate the factors associated with ketamine use. Results: A total of 4658 patients met inclusion criteria. The annual incidence of ketamine use increased from 5% to 28% over the study period ( P  < 0.0001). In the logistic regression analysis, the presence of an emergency physician as a team leader was the strongest predictor of ketamine use (odds ratio [OR] 1.83, 95% confidence interval [CI] 1.44–2.34). The OR for an increase in one point on the Glasgow Coma Scale was 1.10 (95% CI 1.07–1.12), whereas an increase of 1 mmHg of systolic blood pressure had an OR of 0.98 (95% CI 0.98–0.99). Intubation occurring in a major referral hospital had an OR of 0.68 (95% CI 0.56–0.82), while trauma conferred an OR of 1.38 (95% CI 1.25–1.53). Conclusions: Ketamine use increased between 2010 and 2015. Lower systolic blood pressure, the presence of an emergency medicine team leader, trauma and a higher Glasgow Coma Scale were associated with increased odds of ketamine use. Intubation occurring in a major referral centre was associated with lower odds of ketamine use.